DeMark indicators - Perl, Jason; Wiley eBooks (New York : Bloomberg Press/Wiley, 2008)
"Tom DeMark, creator of the widely known and respected DeMark indicators, served as mentor to author Jason Perl. Perl defines and explains how the indicators bring a successful trading decision to conclusion, and offers aggressive or conservative alternative indications. With a chart or graphic explaining each indicator and a foreword by Tom DeMark"--Provided by publisher.
About DeMark indicator trademarks -- TD sequential : defining the trend and identifying exhaustion points -- TD combo -- TD D-wave -- TD lines -- TD retracements -- TD trend factor and TD propulsion -- TD oscillators -- TD moving averages -- TD range projection, TD range expansion breakout, and TD channels -- Short-term indicators: TD differential, TD reverse differential, and TD anti-differential -- TD Waldo patterns -- Putting it all together -- Learning the DeMark indicators.
John Wiley and Sons
Keywords: Investment analysis; Stock price forecasting; Financial instruments -- Prices -- Forecasting; BUSINESS & ECONOMICS -- Investments & Securities -- General; Financial instruments -- Prices -- Forecasting; Investment analysis; Stock price forecasting; Aktienkursprognose; Finanzinstrument; Investitionsanalyse; Electronic books